Discursive Constructions of International Education: How University Lecturers ’Talk’ about International Students - Kastberg, Peter; Tange, Hanne (HERMES - Journal of Language and Communication in Business, 2014)
There is seemingly no end to the difficulties that can arise in the international classroom. Stories abound about issues such as silence, students’ reticence, learner autonomy (or lack thereof), which seem to suggest an unsuccessful transfer of academic knowledge and skills across tasks, contexts and cultures. The current paper will neither offer another problem for us to ponder, nor another solution to the proverbial us-them divide. Instead we shall explore the possible frames of reference that underpin this appreciation of ’the problematic Other‘ in the international classroom. Our central argument is that ‘the problematic Other‘ in international education, here personified by international exchange students, is discursively constructed by university lecturers and students. Among the discursive constructions we see as particularly problematic are those of knowledge ‘transfer’ and ’gap‘ which are consequently examined and deconstructed as part of our discussion. Instead we propose that the new discursive constructions of knowledge ’transformation‘ and ’asymmetry‘ be used. Our initial presuppositions concerning ’discourses of deficit‘ are tested in the analysis. Through an examination of qualitative research interviews with lecturers involved in international teaching, we demonstrate how the problematic discursive constructions of ’gap‘ and ’transfer‘ can be found in the way lecturers talk about their students, but also how at least some respondents embrace the more inclusive idea of transformation. This leads to a concluding discussion in which we suggest that a change in the way we talk and write about international education and students can result in a heightened sensitivity when it comes to understanding and appreciating the practices of ‘the problematic Other’.